A phase 1, multicentre, open-label study to evaluate ovarian follicular activity and hormone levels with an extended-regimen combined oral contraceptive with low-dose ethinyl estradiol supplementation. (August 2015) - Kroll, Robin; Seidman, Larry; Ricciotti, Nancy; Howard, Brandon; Weiss, Herman
Abstract: Objectives To evaluate the effect on ovarian follicular activity of the 91-day extended-regimen combined oral contraceptive (COC), consisting of 84 days of levonorgestrel (LNG)/ethinylestradiol (EE) 150 μg/30 μg tablets plus seven days of EE 10 μg tablets in place of placebo. Methods This was a phase 1, open-label study. Ovarian follicular activity was classified via the Hoogland and Skouby method. Safety and tolerability as well as return to ovulation were assessed. Results Of the 35 subjects included in the efficacy analysis, luteinized, unruptured follicles, or ovulation were detected in 0 of 35 cycles during the first 28-day interval; 1 of 35 cycles (2.9%) in the second 28-day interval; and 2 of 35 cycles (5.7%) in the final 35-day interval. The ovarian activity rate over the entire 91-day treatment period was 2.9%. There was a low incidence of treatment-emergent adverse events. Ovulation returned in most subjects (77.1%, 27/35) within 32 days following the last dose of COC. Conclusions The 91-day extended-regimen COC with low-dose EE supplementation was found to be effective in suppressing ovarian activity and inhibiting ovulation and was well tolerated. Return to ovulation was rapid, occurring within approximately one month after discontinuation of COC. Chinese Abstract 摘要： 目的： 评估91天扩展方案的复方口服避孕药对卵巢卵泡活性的影响，包括84天的左炔诺孕酮/炔雌醇（剂量分别为150ug/30ug）, 剩余7天使用炔雌醇10ug代替安慰剂。 方法： 这是一项1期的开放式研究。卵巢卵泡活性分类采用Hoogland 及Skouby方法。并评估药物的安全性、耐受性及恢复排卵的情况。 结果： 有效性分析纳入35名研究对象，卵巢卵泡活性包括未破裂卵泡黄素化或排卵发生。在第一个28天内，其发生率为0/35，在第二个28天内，监测的未破裂的黄素化卵泡或排卵发生率为1/35（2.9%），在最后的35天内，监测的未破裂的黄素化卵泡或排卵发生率为2/35（5.7%）。 在91天的整个治疗期内，卵巢的活动率为2.9%。治疗中出现的不良事件发生率低。停止服用复方口服避孕药后32天内大部分人恢复排卵（77.1%，27/35）。 结论： 补充小剂量炔雌醇的91天扩展方案的复方口服避孕药能有效抑制卵巢活力，抑制排卵，耐受性好。停用复方口服避孕药后排卵恢复快，几乎在一个月内恢复排卵。